A little bit of Africa in Brazil: ethnobiology experiences in the field of Afro-Brazilian religions - Albuquerque, Ulysses Paulino (BioMed Central, 2014)
This essay, which is the fourth in the series “Recollections, Reflections, and Revelations: Ethnobiologists and Their First Time in the Field”, is a personal reflection by the researcher on his first field experience with ethnobiology of so called Afro-brazilian cults. The author recounts his feelings and concerns associated with initial fieldwork.